Toxicidade de Pesticidas Utilizados na Cultura do Pessegueiro para Estágios Imaturos de Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Giolo, Fabrizio; Grützmacher, Anderson; Manzoni, Cristiane; Härter, Wagner; Müller, Cristiane; Castilhos, Rodolfo (BioAssay, 2009)
One of the most promising biological agent to control Grapholita molesta (Busck) and Argyrotaenia sphaleropa (Meyrick) (Lepidoptera: Tortricidae) in peach orchards in Brazil is the egg parasitoid Trichogramma pretiosum Riley. Nevertheless, there is little knowledge on the toxicity of the pesticides commonly used in peach orchards on this parasitoid. Thus, the toxicity of the pesticides (commercial name - g or ml of commercial product.100L-1) abamectin (Vertimec 18 CE - 80), carbaryl (Sevin 480 SC - 360), deltamethrin (Decis 25 CE - 40), sulphur (Kumulus DF - 600), ethofenprox (Trebon 100 SC - 150), fenthion (Lebaycid 500 - 100), phosmet (Imidan 500 WP - 200), glyphosate (Glifosato Nortox - 6 L.ha-1), glufosinate-ammonium (Finale - 2 L. ha-1), malathion (Malathion 1000 CE - 200), mineral oil (Assist - 2000) and trichlorphon (Dipterex 500 - 300) was evaluated to immatures stages of parasitoid under laboratory conditions. Additionally water was used as the control. The bioassays were carried out by direct application of Pesticides on eggs of Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) containing the immature stages egg-larva, pre-pupa and pupa of T. pretiosum. The reduction on adult emergence compared with the control was used to measure the effect of the chemical. Pesticides were then classified in four categories, according to IOBC/WPRS. The insecticide carbaryl was slightly harmful to egg-larva and pupa stages and moderately harmful to pre-pupa stage. The insecticide malathion was harmless to egg-larva and pre-pupa stage and slightly harmful to pupa stage. The other pesticides were harmless to immature stages of T. pretiosum, so that they can be used for the control of pests in peach orchards with this parasitoid.